2003
DOI: 10.1093/intqhc/mzg042
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal and organizational dimensions of patient satisfaction: the moderating effects of health status

Abstract: The findings provided support for Donabedian's model. They demonstrated that attributes of providers and settings are major components of patient satisfaction, and showed that the scale is a reliable and valid measure of patient satisfaction for this South African population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
122
7
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(150 citation statements)
references
References 31 publications
13
122
7
8
Order By: Relevance
“…These results are consistent with those of other studies which reported lower levels of satisfaction with the organisational quality of care among consumers with health problems. 9,16,23 According to the adopted theoretical model from Andersen & Davidson 1 (1997), and that proposed by Donabedian 3 (1988), we expected correlations between satisfaction with dental care services and level of education, income and skin colour according to user's self-reported race. However, in this study and in another carried out in Taiwan, the service users' levels of education did not correlate with satisfaction with care received.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These results are consistent with those of other studies which reported lower levels of satisfaction with the organisational quality of care among consumers with health problems. 9,16,23 According to the adopted theoretical model from Andersen & Davidson 1 (1997), and that proposed by Donabedian 3 (1988), we expected correlations between satisfaction with dental care services and level of education, income and skin colour according to user's self-reported race. However, in this study and in another carried out in Taiwan, the service users' levels of education did not correlate with satisfaction with care received.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of the health care is determined, up to a point, by the service user's satisfaction with the service provided, and a satisfi ed consumer is more likely to make use of the health service, follow the recommended treatment and stay in contact with the care provider. 20,23 Consumers' satisfaction with the care received is considered to be a parameter for analysing health service outcomes. 5 The level of satisfaction with dental services among the elderly people we evaluated was high, and higher still with those who accesses services offered by the SUS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The methodology should be used in private (without funding from government) For-profit Orthopedic Hospital in Latvia that is consistent for results, as it should help to determine potential areas for progress. Moreover, satisfied patients are likely to return, to fulfil medical treatment requirements achieving better clinical results, as well as to recommend the hospital to others contributing to better overall performance of the organization (Westaway et al, 2003). __________________________________________________________________________ 2017 / 30 19 The tool is based on best-practice approaches in a number of Western European countries and in the United States of America.…”
Section: Methodsmentioning
confidence: 99%